Работоспособность нитридборных сверхтвердых композитов по стандартному регламенту стойкостных испытаний - Гуцаленко, Юрий Григорьевич (Лира, 2015)
The problem of comparing the operational capabilities of the tool materials in the conditions of use of each of them in their recommended area and its system of standard cutting conditions and regulatory stability is considered. The calculation is made for the rating of the standard group of superhard composites based on cubic boron nitride.
Keywords: кубический нитрид бора; обработка механическая; резание; сталь; инструмент лезвийный